Peningkatan Pengetahuan Siswa Sekolah Dasar Tentang Bahaya Buang Air Besar Sembarangan Dengan Metode Bakisah Bahasa Banjar Di Sekolah Dasar Negeri Sungai Telan Besar 1 - Indrayadi, Indrayadi; Yuhansyah, Yuhansyah; Lestari, Putri; Fatimah, Siti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
This community service aims to enhance the knowledge of elementary school students about the dangers of open defecation using the Bakisah Bahasa Banjar method. This method is chosen for its effectiveness in capturing children's attention and delivering messages in an enjoyable manner. The Bakisah Bahasa Banjar method involves the introduction of imaginative characters exploring the consequences of improper waste disposal. Through storytelling, children are guided to understand its negative impacts on health, the environment, and society. This community service contributes positively to cultivating a generation that cares about cleanliness and public health through a cultural approach to promote health independence.